Avaliação da disponibilidade hídrica na sub-bacia do boi branco através do balanço hídrico climatológico e de cultivo - Sales, Mariana Alexandre de Lima [UNESP]; Sánchez Román, Rodrigo Máximo [UNESP]; Sinobas, Leonor Rodríguez; Monteiro, Raimundo Nonato Farias [UNESP]; de Souza, João Victor Ribeiro da Silva [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2017)
One way to calculate the amount of water in a determined system is by means of the water balance, an important tool for the assessment of the water cycle in a specific region. The main goal of this work was to establish the water balance in the watershed Boi Branco-SP, so that it can be used as a tool for the hydro-agricultural and environmental planning of the region. For the climatic water balance, data of the historical series of the region (1971 - 1995) were used. Evapotranspiration data were estimated by the Thornthwaite method. The climatic water balance showed total annual water deficit of 10.1 mm, and surplus of 319.7 mm, with January presenting surplus of 92.6 in the average monthly precipitation; given that the effective monthly precipitation presenting probability of 75%, water deficit in the soil is 238.8 mm and surplus is 56.8 mm. When these data are added to the ones of the crop, as a crop coefficient and soil humidity depletion factor, it is observed that all crops studied showed water deficit in all the months covered.
Assessment of water availability at boi branco watershed through climatic water balance and growing
Keywords: Evapotranspiration; Water agricultural planning; Water capability available in the soil